Comparative Analysis of Student Learning Outcomes in Al-Qur'an Hadith Lessons Based on Learning Media - Miftah Hur Rahman Zh; Muh. Ihsan Yudha Pradana; Purnomo; Yerry Soepriyanto; Fatih Budiman (al-Afkar, Journal For Islamic Studies, 2025)
In the era of technological advancement, technology-based media such as online flipbooks and PowerPoint presentations can potentially enhance the effectiveness of students' learning outcomes in Quran and Hadith studies. However, there is currently no research comparing the differences in learning outcomes based on the use of these two media. Therefore, this study aims to determine whether there is a significant difference in students' learning outcomes based on the use of flipbook and PPT as learning media. This research is a quantitative research with two independent variables and one dependent variable. The target of this research is the students of class XA and XB at Madrasah Aliyah Negeri Kota Batu, with a population sample of 50 students. The analysis in this study utilizes quantitative descriptive statistical methods and the One-Way ANOVA test. The research findings indicate that the significance value of 0.001 < 0.05, which means there is a significant difference in learning outcomes between the class that uses flipbook media and the class that uses PPT.